AMERICAN COLONIES AND THE BRITISH EMPIRE, 1607-1783. (ABINGDON)
1 online resource
Keywords: This first part of an eight-volume reset edition, traces the evolution of imperial and colonial ideologies during the British colonization of America. It covers the period from the founding of the Jamestown colony in Virginia in 1607 to 1764.